English language training for academic and specific purposes for advanced computing education - Satchell, Ray (Zielona Góra: Uniwersytet Zielonogórski)
As part of the TEMPUS Joint European Project for Advanced Computing Education, the University of Bristol Language Centre was asked to provide a specialist English language training programme for students and staff from the Technical University of Wroclaw and the Higher College of Engineering in Zielona Gora.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka